Comparative studies on mechanical properties and dehydrochlorination of chlorinated natural rubber-based composites containing carbon nanotubes and graphene through DFT and experiments. (21st October 2022) - Geng, Haohao; Gu, Haifeng; Wang, Danyang; Li, Wenzhuo; Luo, Ruiyi
ABSTRACT: This study employed a combination of density functional theory (DFT) and experimentation to compare the mechanical properties of chlorinated natural rubber (CNR)/carbon nanotubes (CNT) and CNR/graphene composites and to illuminate their thermal stability differences related to dehydrochlorination. The results showed that, in tensile tests, the Young's modulus of CNR/graphene was greater than that of CNR/CNT, while in pull-out simulation tests, the interfacial shear strength of CNR/graphene was smaller than that of CNR/CNT. In thermal stability tests, both CNT and graphene made the CNR dehydrochlorination reaction rate constant larger, with the thermal stability of CNR/graphene better than that of CNR/CNT. The performance change trends of the two composites were calculated using DFT and the experimental results were consistent with these trends.